2022
DOI: 10.3390/polym14102012
|View full text |Cite
|
Sign up to set email alerts
|

Bond Performance of Steel Bar and Fly Ash-Based Geopolymer Concrete in Beam End Tests

Abstract: This paper presents a comprehensive investigation of the bond characteristics of steel bar reinforced geopolymer concrete (GPC). The ASTM A944 beam end tests were conducted on GPC beams reinforced with plain or ribbed bars. The bond–slip curves and the bond strength of GPC beams were obtained. The relationship between the bond stress and relative slip in plain and ribbed bar reinforced GPC has been represented by empirical formulae. The bond testing results were compared with those of corresponding ordinary Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…It can be seen from Figure 12 that although the bond strength of the ASC specimens is similar to that of the OPC specimens at each corrosion level, the bond stiffness of the ASC specimens is much higher than the OPC specimens. This finding is consistent with other research conducted on non-corroded steel bar [ 7 , 16 , 27 ]. Depending on the failure mode, the nonlinear part ends with a softening branch or a sudden drop.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It can be seen from Figure 12 that although the bond strength of the ASC specimens is similar to that of the OPC specimens at each corrosion level, the bond stiffness of the ASC specimens is much higher than the OPC specimens. This finding is consistent with other research conducted on non-corroded steel bar [ 7 , 16 , 27 ]. Depending on the failure mode, the nonlinear part ends with a softening branch or a sudden drop.…”
Section: Resultssupporting
confidence: 93%
“…The average bond strength over the bond length is calculated as per Equation (3) [ 7 ]: where F is the pull-out force; D is the diameter of the steel bar; and l is the anchorage length between the steel bar and concrete.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and alkaline activators (alkali silicates and/or hydroxides) [ 11 ]. The CO 2 emission during the manufacture of these alternative types of cement could be up to 5–6 times lower relative to PC [ 12 ] in addition to some of the features, such as good mechanical strength, a dense pore structure [ 13 ], thermal resistance [ 14 , 15 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Limestone-based AAC have been reported to develop compressive strength by the formation of C-S-H and N-C-S-N hydration products intermixed with carbonates and silica gel N-S-H (15-25 MPa after 360 days) [18], while waste glass-based AAC have been reported to form C-S-H intermixed with a silica gel (15-29 MPa after 28 and 180 days) [19]. Investigations of AAC in waste glass incorporating limestone as a precursor and as an aggregate [20] have indicated that the limestone participated physically and chemically in the reaction process, densifying the microstructure and enhancing its mechanical properties and stability underwater (15)(16)(17)(18)(19)(20) MPa at 90 days). On the other hand, based on the above-blended types of cement, PC-limestone has been modified with an alkaline activator synthesized from waste glass, resulting in a novel alternative "green" cement, which could reach 50 MPa in compressive strength after 90 days [21].…”
Section: Introductionmentioning
confidence: 99%